Analisis Standar Nasional Indonesia Bidang Perpustakaan dan Bidang Dokumentasi di Indonesia - Rochani Rahayu; Noer'aida Noer'aida (Jurnal Gema Pustakawan, 2023)
The research aims to find out; 1) Number of SNIs in the library and documentation sector in Indonesia; 2) Number of valid and invalid SNIs; 3) Number of available and unavailable full text of SNI; 4). SNI made by adoption and not adoption. The keyword "library" was used to obtain 14 titles and "documentation", as many as 36 titles, after reading it was found that 1 title was the same as SNI library. Research results: SNI field of library 14 titles, 9 titles (64.28%) are still valid, and 5 titles (35.72%) are not valid. SNI Library 4 SNI documents (35.72%) are not available in full, and 9 SNI documents (64.28%) are available in full text pdf. A total of 6 SNI (42.85%) libraries were made by adoption and 8 titles (57.15%) were made not by adoption. There are 35 SNI titles in the field of documentation, and as many as 33 (94.28%) are still valid, and 2 SNI titles (5.72%) are no longer valid. A total of 22 SNI titles in the field of documentation (62.85%) are available in full text, but 13 titles (37.15%) are not available in full text. SNI documentation made by adoption 26 titles (74.29%), and non-adopted 9 titles (25.71%). It was concluded that not all of the SNI in the field of library and documentation are still valid, not all of which are available in full text. Most SNIs in the library field are made using non-adoption methods, while SNI in the documentation field are mostly made by adoption. It is suggested to BSN to complete SNI which does not have full text.